Genomic DNA fingerprinting by restriction fragment end labeling. - van Steenbergen, T J (1995)
A typing method for bacteria was developed and applied to several species, including Escherichia coli and Actinobacillus actinomycetemcomitans. Total genomic DNA was digested with a restriction endonuclease, and fragments were enabled with [alpha-32P]dATP by using the Klenow fragment of DNA polymerase and separated by electrophoresis in 6% polyacrylamide/8 M urea (sequencing gel). Depending on the restriction endonuclease and the bacterium, the method produced approximately 30-50 well-separated fragments in the size range of 100-400 nucleotides. For A. actinomycetemcomitans, all strains had bands in common. Nevertheless, many polymorphisms could be observed, and the 31 strains tested could be classified into 29 distinct types. Furthermore, serotype-specific fragments could be assigned for the three serotypes investigated. The method described is very sensitive, allowing more distinct types to be distinguished than other commonly used typing methods. When the method was applied to 10 other clinically relevant bacterial species, both species-specific bands and strain-specific bands were found. Isolates from different locations of one patient showed indistinguishable patterns. Computer-assisted analysis of the DNA fingerprints allowed the determination of similarity coefficients. It is concluded that genomic fingerprinting by restriction fragment end labeling (RFEL) is a powerful and generally applicable technique to type bacterial species.